Sensitivity of SARS-CoV-2 Variants to Neutralization by Convalescent Sera and a VH3-30 Monoclonal Antibody - Yue, Shuai; Li, Zhirong; Lin, Yao; Yang, Yang; Yuan, Mengqi; Pan, Zhiwei; Hu, Li; Gao, Leiqiong; Zhou, Jing; Tang, Jianfang; Wang, Yifei; Tian, Qin; et al. (Frontiers in Immunology, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic of novel corona virus disease (COVID-19). Though vaccines and neutralizing monoclonal antibodies (mAbs) have been developed to fight COVID-19 in the past year, one major concern is the emergence of SARS-CoV-2 variants of concern (VOCs). Indeed, SARS-CoV-2 VOCs such as B.1.1.7 (UK), B.1.351 (South Africa), P.1 (Brazil) and B.1.617.1 (India) now dominate the pandemic. Herein, we found that binding activity and neutralizing capacity of sera collected from convalescent patients in early 2020 for SARS-CoV-2 VOCs, but not non-VOC variants, were severely blunted. Furthermore, we observed evasion of SARS-CoV-2 VOCs from a VH3-30 mAb 32D4, which was proved to exhibit highly potential neutralization against wild-type SARS-CoV-2. Thus, these results indicated that SARS-CoV-2 VOCs might be able to spread in convalescent patients and even harbor resistance to medical countermeasures. New interventions against these SARS-CoV-2 VOCs are urgently needed.